Pilgrims on wheels: the Pennells, F. W. Bockett, and literary cycle travels - Buchanan, Dave (My University, 2016)
Laurence Sterne, eighteenth- century author of Tristram Shandy and A Sentimental Journey through France and Italy, never rode a tricycle. He couldn’t have. The earliest prototype of bicycles and tricycles, the Draisine or hobbyhorse, wasn’t invented until after 1810, fifty years after Sterne died. But according to early cycle-travel writers Elizabeth Robins Pennell and Joseph Pennell writing in 1887, Sterne would surely have appreciated leisure cycle travel, at least in the Pennells’ tandem-tricycle style; for it was, they claim, perfectly suited to Sterne’s meandering, sentimental disposition. In the dedicatory letter to the long- dead Sterne in Our Sentimental Journey through France and Italy, the Pennells claim that Sterne would have preferred cycle travel even to a railway carriage and that on a tandem tricycle with its two seats, Sterne “would still have a place for ‘the lady,’” a sly nod to the flirtatious tendencies of Sterne’s narrator in A Sentimental Journey, Mr. Yorick.
Keywords: cycle travel; travel writers; cycle-travel writing; cycling history